Assessment of the depth of myometrial invasion in stage I endometrioid endometrial cancer using pancytokeratin immunohistochemistry. Issue 4 (1st June 2004) - Alexander-Sefre, F.; Singh, N.; Ayhan, A.; Thomas, J. M.; Jacobs, I. J.
Abstract : Background: There is a strong correlation between disease mortality and the depth of myometrial invasion in stage I endometrial cancer (EC). Current assessment of the depth of invasion relies on light microscopy. Tumor cells can evade detection by light microscopy if they are vastly outnumbered by myometrial cells. Immunohistochemical (IHC) techniques against pancytokeratins (PCKs) have a great potential in the detection of such isolated cells. Objectives: To investigate the application of IHC techniques in the identification of isolated infiltrating tumor cells within myometrium and assess its significance in clinically stage I EC. Methods: A single representative tissue block containing the deepest myometrial invasion by the tumor was selected for 90 patients with stage I EC. Sections from each block were immunostained in accordance with established streptavidin–biotin peroxidase method using a mouse monoclonal antikeratin clone AE1/AE3. Myometrium was re-examined to identify deeper myometrial invasion that had escaped detection on hematoxylin and eosin (H&E) section. The clinical records were reviewed, and following data were collected: age, race, parity, presentation, associated medical disorders (obesity, diabetes, and hypertension), use of tamoxifen or hormone replacement therapy, menopausal state, recurrence, and survival. Results: Of 90 cases, deeper myometrial invasion was detected on IHC sections in seven cases (7.7%). In five of these seven cases, isolated tumor cells surrounded by inflammatory cells were noted 0.2–1.2 mm deeper within the myometrium than that detected by H&E staining. In the remaining two cases, the deeper extension seen was the result of examining serial levels through the tumor block; in these cases, deeper infiltration should have been apparent on H&E sections. Follow-up data was available in 72 of the 90 cases. A trend was noted between the presence of isolated tumor cells deeper within myometrium on IHC and tumor recurrence ( P = 0.056). The 2-year recurrence-free survival was 40% for the group with IHC evidence of deeper invasion compared with 89% for the group without ( P = 0.005). Similarly, analysis of cause-specific and overall survival revealed significant differences between the two groups ( P = 0.038 and P = 0.026, respectively). Conclusions: In this study, we have shown that it is possible to identify deeper level of myometrial invasion by tumor cells using an IHC technique. IHC-detected deeper invasion is an uncommon event and may be a feature of more aggressive tumors with greater potential for recurrence and lower survival.